The Gaia view of the Cepheus flare. Issue 4 (24th May 2021) - Szilágyi, Máté; Kun, Mária; Ábrahám, Péter
ABSTRACT: We present a new census of candidate pre-main-sequence stars in the Cepheus flare star-forming region, based on Gaia  EDR3 parallaxes, proper motions, and colour–magnitude diagrams. We identified new candidate members of the previously known young stellar groups associated with NGC 7023, L1177, L1217/L1219, L1228, L1235, and L1251. We studied the 3D structure of the star-forming complex and the distribution of tangential velocities of the young stars. The young stellar groups are located between 330 and 368 pc from the Sun, divided into three kinematic subgroups, and have ages between 1 and 5 million yr. The results confirm the scenario of propagating star formation, suggested by previous studies. In addition to the bulk pre-main-sequence star population between 330 and 370 pc, there is a scattered and more evolved pre-main-sequence population around 150–180 pc. We found new candidate members of the nearby Cepheus Association, and identified a new moving group of 46, 15–20 million yr old pre-main-sequence stars located at a distance of 178 pc, around the A0-type star HD 190833. A few pre-main-sequence stars are located at 800–900 pc, indicative of star-forming regions associated with the Galactic local arm above the Galactic latitude of +10°.